The link between adherence to antihypertensive medications and mortality rates in patients with hypertension: a systematic review and meta-analysis of cohort studies - Xuemei Peng; Lihong Wan; Benkai Yu; Jianhui Zhang (BMC Cardiovascular Disorders)
Abstract Background Hypertension (HTN) significantly contributes to cardiovascular disease (CVD) and mortality. This systematic review and meta-analysis specifically investigates how different levels of adherence to antihypertensive therapy (AHT) affect mortality rates in HTN patients. By synthesizing cohort studies, it aims to enhance understanding and inform clinical practices to improve outcomes in hypertensive populations. Methods Our meta-analysis employed a comprehensive search strategy using keywords related to hypertension, medical adherence, and mortality across PubMed, Scopus, and Web of Science, up to July 2024. The eligibility criteria focused on cohort studies linking AHT adherence to mortality. The Newcastle–Ottawa Scale (NOS) was used to assess the risk of bias (ROB). Quantitative analyses involved hazard ratios (HR) and confidence intervals (CI), with an 80% adherence threshold. Subgroup and meta-regression analyses were also conducted using STATA-17 to explore various outcome factors. Results From initial 1,999 studies 12 cohort studies included in our analysis. All included studies had low ROB score. A meta-analysis of 12 studies involving 2,198,311 patient with HTN revealed that poor adherence to treatment significantly increased all-cause mortality (HR: 1.32 [1.14, 1.51], p < 0.001) with high heterogeneity (I²: 98.73%). Additionally, an analysis of four studies with 1,695,872 patients indicated that low adherence was linked to elevated cardiovascular mortality (HR: 1.61 [1.43, 1.78], p < 0.001), showing moderate heterogeneity (I²: 49.51%). Conclusions The study found that poor adherence to AHT significantly increases overall and cardiovascular mortality risk, underscoring the need for improved compliance strategies. Limitations like inconsistent definitions, observational biases, and varying follow-up durations necessitate further research to validate these findings. Clinical trial number Not applicable.